Ethical Digital Technology in Practice - Rogerson, Simon (Milton : Auerbach Publishers, Incorporated, 2022)
This is an important book. Ethics is not an easy topic, and arguably the ethics of IT is less so--not leastdue to its potential for developing and evolving in ways that are either unforeseen or unimaginable . . . . Use this book as a practical resource, an informative and educational source of material in developing expertise, but also as an invaluable toolkit to support practical application of ethical thinking. --Declan Brady, President of the Irish Computer Society and a member of the Board of Directors of the Council of European Professional Informatics Societies Digital technology is about people. It is about those who plan, develop and implement applications which other people use and are affected by. It is about the impact on all these people as well as on the world at large. Ethical Digital Technology in Practice takes a real-world perspective to explore these impacts over time and discover ways in which to promote ethical digital technology through good practice. It draws upon the author's published articles in trade magazines, professional journals and online blogs. These are synthesised into a blueprint which addresses, in a practical manner, the societal issues surrounding the increasing use and abuse of digital technology. It is a follow-up book to the author's book The Evolving Landscape of Ethical Digital Technology, which has a researcher's perspective. This book is a hands-on account of the computer revolution from 1995 to the current day when the world is increasingly dependent on digital technology. It explores some of the social and ethical issues that are part of this revolution. This is not a book about deep philosophical and technical concepts. Nor does it claim to be comprehensive. It is the author's personal account of technological change and its effects on people. It is written by a boy who was smitten by computer technology at the age of 15, became a computer professional and subsequently spent many years showing young people how to develop and use digital technology in a good way. It is a book based upon the author's engagement with practitioners, academics and students during the period as well as his continued fascination with this fantastic technology. Ethical Digital Technology in Practice is a book about the real world, of what has happened and what might happen as digital technology continues to pervade.
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: COMPUTERS / Social Aspects / General; COMPUTERS / General; Internet -- Moral and ethical aspects; Computer science -- Moral and ethical aspects; Information technology -- Moral and ethical aspects